The Relationship of Online Game Addiction with Aggressive Behavior for Teenagers at SMP Negeri 3 Banyumas - Amalia Winahyu Adani; Noor Yunida Triana; Murniati Murniati (Universitas Ibn Khaldun Bogor, 2024)
There is a lot of verbal and physical aggression in online games today. Playing games with a high level of violence can lead to an increase in hostile attitudes and actions. The purpose of this study was to determine whether there is a relationship between online game addiction and the aggressive behavior of grade VIII students at SMP Negeri 3 Banyumas. This study is a correlational study using a cross-sectional approach. The population in this study consisted of 92 grade VIII students of SMP Negeri 3 Banyumas who played online games. A sample of 75 respondents was taken using a simple random sampling technique. The questionnaire was used as a data collector and analyzed with the Spearman rank correlation test. The results showed that most online game addicts were in the mild category (80%), most showed moderate aggressive behavior (62.7%), and there was a strong relationship between online game addiction and aggressive behavior class VIII SMP Negeri 3 Banyumas with a p-value of 0.000 (p-value <0.05; r = 0.579). This indicates that online game addiction can affect a person's aggressive behavior, the higher the level of online game addiction, the more aggressive behavior it leads. This research is expected to be a reference for pediatric nursing.